(untitled) (Research, Society and Development, 2023)
Vitamin B12 is a micronutrient not synthesized by the human body, in which it is of fundamental importance in reactions essential to the formation of new tissues in the body. Found primarily in animal foods, vegetarians and vegans are susceptible to this micronutrient deficiency. Thus, the consumption of vitamin B12 via fortified foods favors accessibility for this public. Vitamin B12 deficiency is reported worldwide and can cause hematological, neurological and cardiovascular disorders, and microencapsulation of the vitamin with prospective applications in food may provide a solution to this problem. The present study aimed to evaluate the viability of microencapsulation of vitamin B12 by spray drying for enrichment of plant-based foods through online and printed bibliographic routes, in the time lapse 1998 to 2023, using descriptors such as: “Vitamin B12”, “Microencapsulation”, “Vegetarian”, “Food Plant-Based”, extracted from several databases such as: Science Direct, Scielo and PubMed, through qualitative content analysis. Thus, it was observed that the isolated subjects that support the hypothesis are well developed and indicate the viability of the proposed objective, but when the search is narrowed, the content is scarce, suggesting too much relevance for this work.